Diversity of Macroalgae in Kasiak Gadang Island Nirwana Beach, Padang - West Sumatra, Indonesia - Hadi, Faisal; Zakaria, Indra Junaidi; Syam, Zuhri (Journal of Tropical Life Science, 2016)
This study had been conducted in October – November 2014. This study aims to know about the diversity of macroalgae in Kasiak Gadang Island, Nirwana Beach, Padang, West Sumatra Indonesia. The method used in this research is line and belt transect. The result of this study is five species of macroalgae founded on this island. There are Padine minor, Sargassum crassifolium, Sargassum cristaefolium, Turbinaria decurrens, and Halimeda sp. Based on relative density, P. minor had 67.15% at Station I and 51.72% at Station II. S. crassifolium had 83.52% at Station III. T. decurrens had 50.86% at Station IV. The index of diversity of macroalgae in Kasiak Gadang Island is about 0.48 – 1.27. According to the diversity index criteria, macroalgae diversity in this island is considered being in low.